Allegations in Navarre (17th century): approach to their bibliographic problems and their cataloguing - Ruiz Astiz, Javier (Revista General de Información y Documentación, 2024)
The bibliographic problems presented by the allegations or porcones when cataloguing them are analysed. In order to show the different cases, we have studied som of the editions printed in 17th century Navarre that have been located in different archives and libraries. All of them have their own peculiarities, and for this reason, guidelines and recommendations are offered for dealing with their cataloguing. The aim of these guidelines is to ensure that bibliographic records provide the most reliable information and the greatest possible amount of data for the use of users.
Keywords: allegations; porcones; printing; cataloguing; bibliography